Ecient Parameter Estimation and Control Based on a Modified LOS Guidance System of an Underwater Vehicle - Elías Revestido Herrero; Francisco J. Velasco; Luis M. Vega; Francisco J. Lastra (Revista Iberoamericana de Automática e Informática Industrial RIAI)
In this work, a methodology is proposed for the improvement of the parameter estimation effciency of a non-linear manoeuvring model of a torpedo shaped unmanned underwater vehicle. For this purpose, data from different tests, were carried out with the aforementioned vehicle at the facilities of the Canal de Experiencias Hidrodinámicas del Pardo, Madrid. In the proposed methodology, the following aspects are taken into account in order to improve the parameter estimation effciency: selection of the sampling period, smoothing of the data acquired in the tests considering a compromise between variance and bias of the smoothing filter to be applied, analysis of the classical linear regression model proposed in each trial, from the statistical point of view for the estimation of the parameters. Improvements in effciency are verified by graphical and statistical methods. In addition, a modification of the conventional LOS method is proposed which provides satisfactory results in the presence of ocean currents by performing a simple procedure.